2019
DOI: 10.1021/acs.jproteome.8b00799
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale, Multi-Center Urine Biomarkers Identification of Coronary Heart Disease in TCM Syndrome Differentiation

Abstract: Coronary heart disease (CHD) threatens human health. The discovery and assessment of potential biometabolic markers for different syndrome types of CHD may contribute to decipher pathophysiological mechanisms and identify new targets for diagnosis and treatment. On the basis of UPLC-Q-TOF/MS metabolomics technology, urine samples of 1072 participants from nine centers, including normal control, phlegm and blood stasis (PBS) syndrome and Qi and Yin deficiency (QYD) syndrome, and other syndromes of CHD, were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The key pathogenesis of CHD is based on the abnormal metabolism of myocardial substrates and the disturbance of energy metabolism induced by myocardial ischemia or hypoxia (Doenst et al, 2013). A recent study found that metabolites involved in the TCA cycle and amino acid metabolism (tryptophan, arginine, and proline metabolism) were significantly decreased in fasting morning urine of CHD patients with Qi and Yin deficiency syndrome, suggesting that the metabolites in amino acid metabolism and TCA cycle were partially the material foundation of Qi (Zhou et al, 2019). In TCM theory, Qi is the commander of blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key pathogenesis of CHD is based on the abnormal metabolism of myocardial substrates and the disturbance of energy metabolism induced by myocardial ischemia or hypoxia (Doenst et al, 2013). A recent study found that metabolites involved in the TCA cycle and amino acid metabolism (tryptophan, arginine, and proline metabolism) were significantly decreased in fasting morning urine of CHD patients with Qi and Yin deficiency syndrome, suggesting that the metabolites in amino acid metabolism and TCA cycle were partially the material foundation of Qi (Zhou et al, 2019). In TCM theory, Qi is the commander of blood.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, metabolic abnormality plays a key role in affecting the development and prognosis of CHD (Nicholson et al, 1999; Kordalewska and Markuszewski, 2015). Recently, it was found that metabolites involved in amino acid metabolism and tricarboxylic acid (TCA) cycle might partially constitute the material foundation of Qi, according to the Qi and blood theory of TCM (Zhou et al, 2019). Therefore, we studied differential metabolites in the serum of CHD patients to explore the effects of TCM on regulating Qi and promoting blood circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Applying metabonomics approaches to material basis study of TCM syndrome differentiation is a beneficial attempt. Metabonomics technology research based on liquid chromatography coupled with mass spectrometry (LC-MS) and gas chromatography coupled with mass spectrometry (GC-MS) has been applied in the TCM syndrome differentiation studies and biomarker identification in coronary heart disease (Zhou et al, 2019) and rheumatoid arthritis (Gu et al, 2012). However, few studies were undertaken to explore the objective material basis of the TCM syndrome differentiation in patients with psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…For item 7 (S3 in the checklist of the RIGHT-TCM), it is recommended to describe whether to treat disease based on the syndrome differentiation of TCM. Syndrome differentiation is an important basic concept of TCM [ [23] , [24] , [25] ]. It is the process of applying “principle-method-recipe-medicines” to clinical practice.…”
Section: Explanation and Discussion About The Right-tcmmentioning
confidence: 99%